IMPLEMENTASI PSAK 109 PADA LAPORAN KEUANGAN BAZNAS KUDUS - Nuralimah, Salma Putri; Fitriyani, Meinda; Na'imah, Mahfifatun Nurul; Rosyidah, Husnur (Jaksya: Jurnal Akuntansi Syariah, 2024)
This research is designed with the aim of knowing the process of recognition as well as measurement of reception and distribution by the Holy BAZNAS. To see how the implementation of the financial statements carried out by the Holy BAZNAS. To understand the compatibility between the financial statements of the Holy BAZNAS with the provisions of PSAK 109. The method used in this research is qualitative descriptive. The results of this research were obtained from the process of gathering data through interviews. The results of this study show that the preparation of financial reports carried out by the Holy BAZNAS has referred to PSAK 109 including the process of receipt and disbursement of zakat funds, infak/sedekah by the holy Baznas. The HolyBaznas always records any economic transactions, and also the presentation of the financial report has been in accordance with the existing provisions as well as the treatment of non-halal funds according to the scripture. In his acknowledgement and presentation, the Holy BAZNAS has been effective and efficient by using a double entry system. Overall, the financial statements carried out by the Holy BAZNAS are in accordance with Rule 109 from the point of view of recognition, measurement, as well as presentation.